Absolute thresholds for the perception of fore-and-aft, lateral, and vertical vibration at the hand, the seat, and the foot - Morioka, Miyuki; Griffin, Michael J. (Journal of sound and vibration, 2008)
Oscillatory motions of handles, seats, and floors produce complex patterns of sensations in the body with the detection of these motions dependent on the sensitivity of the body to the applied vibration. This study examined the effect of input location (the hand, the seat, and the foot) and vibration frequency (8–315 Hz at the hand and foot; 2–315 Hz at the seat) on absolute thresholds for the perception of vibration in each of three axes (fore-and-aft, lateral, and vertical). Perception thresholds were determined with 96 males aged 20–29 years divided into eight groups of 12 subjects; each group received vibration at either the hand, the seat, or the foot in one of the three axes (one group experienced both lateral and vertical vibration at the hand). A frequency dependence in the thresholds was apparent for each of the three directions at each of the three locations; U-shaped acceleration threshold contours at frequencies greater than 80 Hz suggest the same psychophysical channel-mediated high-frequency thresholds at the hand, the seat, and the foot. Among the nine axes, sensitivity was greatest for vertical vibration at the seat at frequencies between 8 and 80 Hz, whereas sensitivity was greatest for vertical vibration at the hand at frequencies greater than 100 Hz. Absolute thresholds for the perception of vibration at the hand, the seat, and the foot are not consistent with the relevant frequency weightings in current standards.